2018
DOI: 10.2298/tsci171023262w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on heat transfer and flow characteristics of two kinds of porous metal foam tubes filled with water

Abstract: The heat transfer and flow characteristics of water in a copper foam tube, a nickel foam tube, and a smooth tube are investigated in this paper. The copper foam tube and nickel foam tube are produced, and an experiment for testing the heat transfer and flow characteristics of water in metal foam tubes is set up. Experimental system validation is done in this paper, and it is found that the experimental results have a good agreement with that of published literature. The effects of two kinds of metal foam tubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The results indicated that the Nusselt number increases with decreasing Darcy number, and it was enhanced over 80% of the fluid case. Wang et al [22] conducted an experimental study on the effects of heat transfer and flow resistance in a tube that had been filled with copper foam and nickel foam, respectively. The dimension of tube length 200mm and diameter 10mm.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the Nusselt number increases with decreasing Darcy number, and it was enhanced over 80% of the fluid case. Wang et al [22] conducted an experimental study on the effects of heat transfer and flow resistance in a tube that had been filled with copper foam and nickel foam, respectively. The dimension of tube length 200mm and diameter 10mm.…”
Section: Introductionmentioning
confidence: 99%